2018
DOI: 10.1093/inthealth/ihy058
|View full text |Cite
|
Sign up to set email alerts
|

‘Then her neighbour will not know her status’: how health providers advocate antiretroviral therapy under universal test and treat

Abstract: Health providers appropriated stigma to encourage early ART. This suggests an attentiveness to the social burden of HIV/AIDS, but potentially exacerbates discrimination and conflicts with efforts to reduce HIV-related stigma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Our findings are consistent with those of Pell et al, who reported that the implementation of the 2015 guidelines took > 12 months to be adopted in all SSA countries after their official release. 1 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with those of Pell et al, who reported that the implementation of the 2015 guidelines took > 12 months to be adopted in all SSA countries after their official release. 1 …”
Section: Discussionmentioning
confidence: 99%
“…Since then, infection with human immunodeficiency virus (HIV) has spread globally and caused an estimated 74.9 million infections and 32 million AIDS-related illnesses. 1 In its first 15 years no treatment could control the infection or halt its spread. 2 By 2018, the African region was home to approximately 25.7 million people living with HIV (PLWH) 1 and in that year alone, Africa experienced approximately 1.1 million new infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative MaxART study on healthcare providers’ perspectives of early ART revealed that health providers were motivating clients to start ART early in order to avoid severe illness and becoming ‘bed ridden’ . Avoiding visibly apparent illness was described as particularly advantageous by providers because it meant that clients could evade disclosing their HIV status to friends and neighbours.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Farmer have been among several prominent anthropologists involved in the formulation and execution of health policies and intervention projects. As such, they are positioned to make a powerful case to the global health community to target the cultures of elite privilege that enable systemic health inequities in addition to -or even instead of -the cultures and behaviours of impoverished people when designing health projects (but see Shaffer 2018).Other global health anthropologists hold valuable positions on the ground -often with little public visibility -where they work to improve local acceptability of global interventions or ensure projects are run in ways that matter to the people whose lives they are intended to shape (de Klerk 2013;Pell et al 2019).Anthropological methods are embraced by several global health projects, which have found ethnography, and qualitative research more generally, crucial to their long-term success (Campbell 2011).…”
mentioning
confidence: 99%